THE IMPACT OF FINANCIAL TECHNOLOGY ON TRANSACTIONAL KNOWLEDGE ACQUISITION AMONG GENERATION Z - Asry Ady Bakri; Dwi Atmojo WP; Muammar Khaddafi; Iwan Henri Kusnadi; Yoseb Boari (Sean Institute, 2023)
This study seeks to investigate the impact of Financial Technology on Generation Z's transactional knowledge and usage, as well as their preferences for using e-wallet applications. Using Google Form, 26 respondents of various ages and genders participated in an online survey to capture data on transactional knowledge and FinTech utilization. The results of the analysis indicate that Generation Z has a solid grasp of Financial Technology, particularly as it pertains to e-wallet applications. The majority of respondents demonstrated a practical understanding of non-cash transactions, but there is still room for improvement in their comprehension of financial concepts. E-wallets are also widely adopted, with the majority of respondents using applications such as Dana, Qris, Ovo, Shopeepay, and Gopay for a variety of transactions, including purchases and fund transfers. However, some respondents continue to rely on cash transactions. Therefore, more comprehensive financial education programs, cybersecurity and privacy awareness campaigns, and the development of more intuitive e-wallet app interfaces are suggested. With the implementation of these recommendations, Generation Z can be better prepared for evolving financial changes and ensure the prudent and efficient use of Financial Technology in their financial management.